Use of Wide-Pore Carbons to Examine Intermolecular Interactions during the Adsorption of Anthraquinone Dyes from Aqueous Solution - Maria Paz Elizalde-González; Virginia Hernández-Montoya (Adsorption Science & Technology)
Carbon samples with low specific surface areas containing both mesopores and macropores were prepared by heating orange seeds to 450, 600, 800 and 1000 °C, respectively. These materials were characterized by ultimate and proximate analysis, thermogravimetry, IR spectroscopy and potentiometric titrations. The raw (unheated) material was acidic, containing a considerable amount of nitrogen but only a small amount of lignin. The carbon samples were basic and exhibited type II or type III nitrogen adsorption isotherms depending on the carbonization temperature. Non-carbonized orange seeds were more effective in the adsorption of anthraquinone dyes (Acid Blue 80, Acid Blue 324, Acid Green 25 and Acid Green 27) from aqueous solution at 25 °C. The moderate adsorption capacities exhibited by the carbonized samples allowed an analysis of the intermolecular interactions between the adsorbents and dyes with similar structures but slightly different hydrophobicities and donor capacities.